Tales from the Dark Side of the City - Unknown Fields; Neasden Control Centre; City Edition Studio (London : AA Publications, 2016)
"Unknown Fields is a nomadic design studio that ventures out on expeditions into the shadows cast by the contemporary city, to uncover the industrial ecologies and precarious wilderness its technology and culture set in motion. Tales from the Dark Side of the City is a book series that forms an atlas to the territories and stories of a city that stretches across the entire planet, a city that sits between documentary and fiction, a city of dislocated sites, of drone footage and hidden-camera investigations, of interviews and speculative narratives, of toxic objects and distributed matter from distant grounds. They are a collection of tales from the constellation of elsewheres that are conjured into being by the city's wants and needs, fears and dreams."--Publisher's note.
[v. 1]. High Strange -- [v. 2]. Snowing in the Supercomputer -- [v. 3]. Treasured Island -- [v. 4]. A World Adrift -- [v. 5]. Never Never Lands -- [v. 6]. The Breastmilk of the Volcano.
boek
Keywords: Urban ecology (Sociology); Sociology, Urban; Black market -- Madagascar; South China Sea -- Commerce; Parapsychology -- United States; Climatic changes -- Alaska; Lithium mines and mining -- Bolivia; Gold mines and mining -- Australia